FORMULASI UNDANG-UNDANG NOMOR 1 TAHUN 1974 DALAM PERSINGGUNGAN ANTARA NEGARA DAN AGAMA - Fenni Febiana (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2017)
With the enactment of Law No. 1 of 1974 on Marriage, the authors noticed that the policy in question is to accommodate the aspirations of the majority Muslims who happen to choose schools of Shafi'i schools and realized in the form of legislation. The hope of course that the values of Islam, which had long color the way of arbitrate Indonesian people, then can have the firmness and recognition from the state. Thus the struggle of Muslims, which in certain portions require the enactment of Islamic law, at least one by one can be realized even with regard to the context Indonesian nation known multi-religious, ethnic and cultural. This is consistent with the theory put forward by the imam, al-Maliki al-mursalah mashlahah which can be translated